The pre-Devonian tectonic framework of Xing’an–Mongolia orogenic belt (XMOB) in north China - Xu, Bei; Zhao, Pan; Wang, Yanyang; Liao, Wen; Luo, Zhiwen; Bao, Qingzhong; Zhou, Yongheng (Journal of Asian earth sciences, 2015)
•A new tectonic division of the Xing’an–Mongolia orogenic belt (XMOB) in north China has been presented.•Four blocks and four sutures have been recognized in the XMOB.•The XMOB belongs to a pre-middle Devonian multiple orogenic belt in the Central Asian Orogenic Belt (CAOB). A new tectonic division of the Xing’an–Mongolia orogenic belt (XMOB) in north China has been presented according to our research and a lot of new data of tectonics, geochronology and geochemistry. Four blocks and four sutures have been recognized in the XMOB, including the Erguna (EB), Xing’an–Airgin Sum (XAB), Songliao–Hunshandake (SHB), and Jiamusi (JB), and Xinlin–Xiguitu (XXS), Xilinhot–Heihe (XHS), Mudanjiang (MS) and Ondor Sum–Yongji sutures (OYS). The framework of the XMOB is characterized by a tectonic collage of the blocks and orogenic belts between them. Different Precambrian basements have been found in the blocks, including the Neoproterozoic metamorphic rocks and plutons in the EB, the Neoproterozoic metamorphic rocks in western and eastern of segments of the XAB, Mesoproterozoic and Neoproterozoic metamorphic rocks in middle segments of the XAB, respectively, the Neoproterozoic metamorphic rocks and Mesoproterozoic volcanic rocks and plutons in the SHB, and Neoproterozoic metamorphic rocks in the JB. The XXS resulted from a northwestward subduction of the XAB beneath the EB during the Cambrian, which was followed by the forming of the XHS and OYS in the northwest and south margins of the SHB in the Silurian, respectively. The MS was caused by a westward subduction of the JB beneath the east margin of the SHB during the middle Devonian. The three Cambrian, Silurian and middle Devonian events indicate that the XMOB belongs to a pre-middle Devonian multiple orogenic belt in the Central Asian Orogenic Belt (CAOB). Forming of the XMOB suggests that the southeast part of the Paleo Asian Ocean closed before the middle Devonian.